2011
DOI: 10.1007/s11274-011-0983-0
|View full text |Cite
|
Sign up to set email alerts
|

Lead and cadmium-induced oxidative stress impacting mycelial growth of Oudemansiella radicata in liquid medium alleviated by microbial siderophores

Abstract: In this study, the effects of siderophores produced by six bacteria on mycelium growth, Cd and Pb accumulation, lipid peroxidation, protein content and antioxidant enzyme in Oudemansiella radicata were investigated in Cd and Pb-containing liquid medium. The results showed that inoculation with siderophore-containing filtrates (SCF) partly enhanced the growth of O. radicata after 15 days, with 0.8-32.4% biomass increase for Cd and 0.7-20.8% for Pb compared to control(s), which lacked siderophore. The maximum en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Similar observation was noted by Dimpka et al (2009a) in cowpea inoculated with S. acidiscabies E13 SPB strain under Ni 2+ exposure. Another study on Oudemansiella radicata treated with the culture filtrates containing siderophores synthesized by 6 different SPB strains demonstrated a significant decline in MDA level within mycelium exposed to Cd 2+ and Pb 2+ (Cao et al, 2012). The above mentioned studies including our results indicate that under HMs contamination, the siderophores can potentially alleviate oxidative stress by binding to free ions of heavy metals.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar observation was noted by Dimpka et al (2009a) in cowpea inoculated with S. acidiscabies E13 SPB strain under Ni 2+ exposure. Another study on Oudemansiella radicata treated with the culture filtrates containing siderophores synthesized by 6 different SPB strains demonstrated a significant decline in MDA level within mycelium exposed to Cd 2+ and Pb 2+ (Cao et al, 2012). The above mentioned studies including our results indicate that under HMs contamination, the siderophores can potentially alleviate oxidative stress by binding to free ions of heavy metals.…”
Section: Discussionsupporting
confidence: 66%
“…It has been observed that the presence of Cd 2+ ions may lead to the ROS production, inducing lipid peroxidation in plants (Mishra et al, 2006;Islam et al, 2008;Xu et al, 2011). The level of MDA is an indicator of the lipid peroxidation in plants and its high accumulation is related to oxidative stress (Cao et al, 2012). In this study, we demonstrated that inoculation with all tested SPB strains considerably decreased the level of MDA accumulation in leaves, stems, and roots of S. viminalis L..…”
Section: Discussionsupporting
confidence: 51%
“…In this regard, iron homeostasis genes, especially involved in high-affinity iron transport ( FET3 and FTR1 ) and siderophore iron transport ( ARN1 , ARN2 , SIT1/ARN3 , ENB1/ARN4 , FIT1 , FIT2 , and FIT3 ; Figure 4) were induced in response to Co 2+ , Mn 2+ , Ni, 2+ and Zn 2+ . Notably, a recent study reported that siderophores can reduce metal toxicity [59]. Induction of the siderophore ion transport system might therefore serve as one further general detoxification mechanism by chelating extracellular metal ions to prevent their uptake.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy cannot be wholly explained by greater assortment within-versus between-species, given that in this study nonproducers were rescued to the same extent by conspecifics and heterospecifics. Further work to explore these opposite responses to selection at genetic and ecological scales will be key to understand long-term responses to shared public goods more generally and to explain the lack of effectiveness in using siderophore producing bacteria (as opposed to the direct addition of siderophores (e.g., Nair et al 2007;Cao et al 2012) to remediate metal-contaminated environments (Wu et al 2006;Kuffner et al 2008;Li and Ramakrishna 2011;Rojas-Tapias et al 2012).…”
Section: Discussionmentioning
confidence: 99%